A pilot program to improve TB care with primary and specialty care coordination in TB public health clinic - P. Jadhav; G. Boudoin; R. Miles; S. Seymour; J. Parham; A. Wolfe; J. Ali (IJTLD Open)
BACKGROUND: The Wetmore Tuberculosis (TB) Clinic in New Orleans serves patients who often lack primary care (PC) or specialty care (SC), which is complicated by comorbidities. An initiative to provide on-site PC and coordinate care aims to enhance TB patient management. METHODS: Data collection involved categorizing patients based on their PC status: Group I (regular PC), Group II (intermittent PC), and Group III (no PC), with on-site Nurse Practitioner-based Bridge Care (NPBC) provided as needed. RESULTS: Over 12 months, 209 out of 354 patients required NPBC and PC/SC coordination, with a 20% shift from Group III to Group I, reducing the need for NPBC. CONCLUSION: The program improved TB care at Wetmore TB Clinic, offering a potential model for other TB clinics to enhance patient adherence and TB and post-TB treatment follow-up.